2010
DOI: 10.1002/mus.21535
|View full text |Cite
|
Sign up to set email alerts
|

HIV neuropathy in South Africans: Frequency, characteristics, and risk factors

Abstract: The purpose was to estimate the frequency, characteristics, and risk factors of HIV-associated distal sensory polyneuropathy (DSP) among South Africans who attend an urban community-based clinic. In a cross-sectional study, neuropathy status was determined in 598 HIV-infected adults using validated tools (Brief Peripheral Neuropathy Screen and a modified version of the Total Neuropathy Score) to categorize subjects as DSP versus no DSP. Symptomatic DSP (SDSP) required the presence of at least two neuropathic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
107
4
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 17 publications
15
107
4
2
Order By: Relevance
“…1 However, World Health Organization guidelines and many national guidelines in resource-limited countries recommend D4T or zidovudine as first-line treatment with recent recommendations to reduce the dose of D4T to 30 mg to minimize adverse events. 2 Several studies from sub-Saharan Africa have also found PN to be a significant side effect in patients receiving D4T-based ART (range = 4.3-56%) [3][4][5][6][7][8]13 and the most common reason for switching regimens because of adverse events. 5 However, use of a validated screen for neuropathy was not reported in most of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, World Health Organization guidelines and many national guidelines in resource-limited countries recommend D4T or zidovudine as first-line treatment with recent recommendations to reduce the dose of D4T to 30 mg to minimize adverse events. 2 Several studies from sub-Saharan Africa have also found PN to be a significant side effect in patients receiving D4T-based ART (range = 4.3-56%) [3][4][5][6][7][8]13 and the most common reason for switching regimens because of adverse events. 5 However, use of a validated screen for neuropathy was not reported in most of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of DSP in our study was 27.4%. It was less than other reported in various countries in Africa [8]- [11] [16]. The difference could be explained by the sample size, the mean age of the populations, the proportion of population on HAART and the diagnosis tool used by authors.…”
Section: Discussionmentioning
confidence: 61%
“…Factors associated with them are the virus itself, opportunistic infections (cytomegalovirus, which rather gives multiple mononeuropathies) and antiretroviral therapy [3] [5]- [7]. The prevalence of sensory polyneuropathy varies greatly according to the criteria used, and may reach 50% [8]- [11]. In Africa the unavailability of electromyography makes diagnosis more difficult, often based on clinical criteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Two recent studies in South Africa reported that about 60% of HIV-positive out-patients on ART had HIV-SN, and over two-thirds of these patients had a painful neuropathy. 6,7 While not fatal, HIV-SN has a significant negative impact on psychological, social and economic well-being 4 and there are no proven treatments for the pain. 8 The pathogenesis of HIV-SN has not been fully explained, but human [9][10][11] and animal studies 12 indicate that inflammation plays a central role.…”
Section: Introductionmentioning
confidence: 99%